Factors Affecting Green Governance with an Emphasis on Ethical Teachings - Reza Mahboobi; Taghi Mohammadi; Samereh Shojaee (Journal of Foresight and Health Governance, 2026)
Green governance, grounded in ethical teachings, emphasizes the incorporation of environmental sustainability and social justice into decision-making processes. It seeks to balance environmental responsibility with ethical standards and ultimately contributes to a more sustainable and just society. The present study aimed to identify the factors affecting green governance with an emphasis on ethical teachings. In terms of purpose, this study is applied-developmental, and it was conducted using a descriptive-survey method. In the qualitative phase, the statistical population consisted of professors, experts, and academics in the field of environmental studies in Iran, of whom 15 were selected through purposive sampling until theoretical saturation was achieved. In the quantitative phase, the statistical population included all managers in the environmental sector in Tehran. Based on the sample-size formula for structural equation modeling used in Kline (2011), 200 participants were selected through convenience sampling (Kline, 2011). Data were collected through semi-structured interviews in the qualitative phase and a questionnaire in the quantitative phase. The data were analyzed using thematic analysis and MAXQDA software in the qualitative phase, and structural equation modeling and PLS software in the quantitative phase. The initial model was designed with 76 initial codes, which were categorized into 14 axial codes. According to the results of exploratory and confirmatory factor analyses, all 76 factors were confirmed as indicators of green governance with an emphasis on ethical teachings. The results indicate that green governance depends on integration among management, economics, technology, government policies, and social participation. The indicators identified in this study can support the development of more effective policies and the improvement of green governance based on ethical principles.